Pelatihan Membuat Pupuk Organik Cair (POC) dari Limbah Kulit Pisang : Pengabdian - Ardian Hangga Kelana; Marice Karubaba; Titia Erika Sarlota Awom; Saul Weipsa; Yekson Soll; Evellyne Binsyowie Sandhiya Mandosir; Midah Nurhidayah; Sakka Irawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service (PKM) activity was titled "Training on Making Liquid Organic Fertilizer (POC) from Banana Peel Waste" at MA Yaa Bunayya Jayapura. The main objective of this PKM activity was to raise students' awareness of environmental protection by making liquid organic fertilizer (POC) from banana peel waste. This community service activity used a participatory approach, actively involving students in every stage of the activity. The methods used were training, lectures, Q&A sessions, group discussions, and presentations. A project-based design was used in this activity because it involved the development of specific projects that could help students, teachers, and the school community through waste management. The results of the PKM activity indicated that training on making Liquid Organic Fertilizer (POC) from banana peel waste can be an effective way to increase students' awareness and skills in environmentally friendly waste management. Thus, this training can benefit students, the school, and the surrounding environment, ensuring a sustainable human life free from banana peel waste. This training also serves as a good example for the community to develop sustainable waste management practices.